The role of right ventricular volume in the diagnosis of pulmonary embolism and morbidity prediction - Tunalı Türkdoğan, Figen; Ertekin, Ersen; Zencir, Cemil; Yazici, Onur; Tuncyurek, Ozum; Çanakçı, Selçuk Eren (Journal of Surgery and Medicine, 2021)
Background/Aim: Pulmonary embolism is a quite common and usually fatal disease. This study aimed to investigate the predictive value of the right ventricular volume in terms of pulmonary embolism and its laterality using imaging techniques. Methods: This case-control study included patients who underwent tomography with a pre-diagnosis of pulmonary embolism between January 2016 and January 2018. The study group included patients diagnosed with pulmonary embolism, while the control group consisted of those with an excluded diagnosis of embolism. The gender, age, echocardiography, right ventricular volume, embolism location, computed tomography results, morbidity, and mortality of the patients were recorded. Among 253 patients who underwent chest tomography with a diagnosis of pulmonary embolism, the data of 149 patients were obtained. There were 64 individuals in the control group and 85 individuals in the patient group. Results: In the study group, the length of hospital stay was 10.0 (range, 15.0-6.0) days, the systolic blood pressure was 125.5 (28.8) mmHg, the diastolic blood pressure was 77.8 (17.8) mmHg, and the heart rate was 103.4 (28.1) min. The ROC analysis of right ventricular volume revealed 81.2% sensitivity and 67.2% specificity (AUC: 0.850; P=0.001; 95% CI 0.789-0.910; cut-off: 103.7) in showing pulmonary embolism. There was a positive correlation between right ventricular volume and D-dimer (r: +0.739, P=0.001) in the control group and no correlation between the two in the study group (r: -0.178, P=0.139). Conclusion: Measuring the right ventricular volume with the software will contribute to the treatment and referral of patients with suspected pulmonary thromboembolism who underwent chest tomography. Thus, time and financial waste can be avoided by preventing unnecessary patient transfers, and early transfer of real patients can contribute to the reduction of mortality and morbidity.